New species of the ant-mimicking genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from Sarawak, Borneo - Yamasaki, Takeshi; Hashimoto, Yoshiaki; Endo, Tomoji; Hyodo, Fujio; Itioka, Takao; Meleng, Paulus (Zootaxa, 2018)
The genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) is one of the most diversified salticid groups in Southeast Asia, with 23 species previously recorded from Borneo. Based on the collections accumulated from 2004 to 2014 in the Lambir Hills National Park, we herein describe six new species: M. amabilis sp. nov., M. hashimotoi sp. nov., M. lagarosoma sp. nov., M. leptosoma sp. nov., M. salaputium sp. nov. and M. tintinnabulum sp. nov. In addition, we describe the female of M. endoi Yamasaki & Ahmad, 2013 for the first time. The male-female combination in M. amabilis sp. nov., M. tintinnabulum sp. nov. and M. endoi were confirmed by DNA barcoding.